2016
DOI: 10.1242/dmm.026849
|View full text |Cite
|
Sign up to set email alerts
|

Heterotypic models of osteosarcoma recapitulate tumor heterogeneity and biological behavior

Abstract: Osteosarcoma (OS) is a heterogeneous and rare disease with a disproportionate impact because it mainly affects children and adolescents. Lamentably, more than half of patients with OS succumb to metastatic disease. Clarification of the etiology of the disease, development of better strategies to manage progression, and methods to guide personalized treatments are among the unmet health needs for OS patients. Progress in managing the disease has been hindered by the extreme heterogeneity of OS; thus, better mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 59 publications
0
30
2
Order By: Relevance
“…Similarly, Tome et al reported 5 × 10 5 143B-LM4 cells per nude mouse was able to generate tumours in immunodeficient [34] . Another study reports the use of the OS-1 and OS-2 canine osteosarcoma cells (1 × 10 5 cells resuspended in 10 µL PBS and intra-tibially injected into nude mice), to assess their tumour characteristics and metastatic features [35] . Finally, Shimozaki et al, injected a suspension of 5 × 10 5 143B cells diluted in Matrigel™, directly into the medullar cavity of the tibia of nude mice [36] .…”
Section: Induction Of Primary Bone Tumour By Cell Injections In Hetermentioning
confidence: 99%
“…Similarly, Tome et al reported 5 × 10 5 143B-LM4 cells per nude mouse was able to generate tumours in immunodeficient [34] . Another study reports the use of the OS-1 and OS-2 canine osteosarcoma cells (1 × 10 5 cells resuspended in 10 µL PBS and intra-tibially injected into nude mice), to assess their tumour characteristics and metastatic features [35] . Finally, Shimozaki et al, injected a suspension of 5 × 10 5 143B cells diluted in Matrigel™, directly into the medullar cavity of the tibia of nude mice [36] .…”
Section: Induction Of Primary Bone Tumour By Cell Injections In Hetermentioning
confidence: 99%
“…Yet studies have shown the opposite to be true, perhaps because young adults are under reduced parental surveillance or have limited knowledge of their own physical health . Instead, certain OS tumors in both humans and dogs may be biologically predetermined to successfully metastasize, regardless of time to diagnosis . Using both human and dog OS, future research should ascertain whether evolutionarily conserved pathways are needed to develop the metastatic OS phenotype, and whether patterns of gene expression could be used to categorize intrinsically aggressive molecular subtypes of OS in both species.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these models are a useful tool for screening drugs [ 29 , 30 ]. Arguably, the induction of OS by intraosseous injection is one of the most relevant murine models for studying this disease, with studies recapitulating OS tumour heterogeneity [ 31 ], as well as providing biological understanding of activation pathways [ 32 ]. The fundamental limitation of this model is the use of mature OS cells, which does not provide information on tumour initiation.…”
Section: In Vivo Animal Modelsmentioning
confidence: 99%